Nitrogen efficiency in hydroponic chicory - Filho, Arthur Bernardes Cecílio [UNESP]; Coelho, Roberto Luciano [UNESP]; da Cunha, Tatiana Pagan Loeiro [UNESP]; Urrestarazu, Et Miguel (Taylor & Francis, 2017)
An experiment was conducted to develop a model of vegetative growth based on the nitrate concentrations in nutrient solutions using the nutrient film technique and to determine the best cultivar for each concentration. The chicory cultivars (“Pão de Açúcar,” “Folha Larga,” “Precoce de Trieste” and “Catalonha”) and the subplots corresponded to different nitrate concentrations (6.68, 10.0, 13.32 and 16.64 mmol L−1). There was an interaction between the evaluated factors, such that there was no similarity in the response of the chicory cultivars to the N concentrations in the nutrient solution. The most productive chicory cultivar was “Pão de Açúcar,” which exhibited 10.5% higher productivity than the average, and the least productive was “Folha Larga,” which showed approximately 8.5% lower productivity than the average.
Keywords: cichorium intybus; growth model; hydroponic systems; mineral nutrition